INVOLVEMENT OF MULTIPLE MOLECULAR PATHWAYS IN THE GENETICS OF OCULAR REFRACTION AND MYOPIA. Issue 1 (January 2018) - Wojciechowski, Robert; Cheng, Ching-Yu
Abstract : Purpose: The prevalence of myopia has increased dramatically worldwide within the last three decades. Recent studies have shown that refractive development is influenced by environmental, behavioral, and inherited factors. This review aims to analyze recent progress in the genetics of refractive error and myopia. Methods: A comprehensive literature search of PubMed and OMIM was conducted to identify relevant articles in the genetics of refractive error. Results: Genome-wide association and sequencing studies have increased our understanding of the genetics involved in refractive error. These studies have identified interesting candidate genes. All genetic loci discovered to date indicate that refractive development is a heterogeneous process mediated by a number of overlapping biological processes. The exact mechanisms by which these biological networks regulate eye growth are poorly understood. Although several individual genes and/or molecular pathways have been investigated in animal models, a systematic network-based approach in modeling human refractive development is necessary to understand the complex interplay between genes and environment in refractive error. Conclusion: New biomedical technologies and better-designed studies will continue to refine our understanding of the genetics and molecular pathways of refractive error, and may lead to preventative and therapeutic measures to combat the myopia epidemic. Abstract : Here, the authors review the results of recent epidemiological and genome-wide association studies into the molecular pathways and genetics underlying ocular refraction and myopia, the prevalence of which is reaching epidemic proportions in East Asia. The authors examine the complex mixture of factors contributing to myopia and discuss strategies for future research.